Public History in China: Is it Possible? - Na Li (Public History Review, 2014)
This article, based on my experience of teaching a graduate seminar in public history at Chongqing University, explores the possibilities of public history in China. It discusses how a reflective and collaborative curriculum works, and its implication for establishing Public History programs in the Chinese context. The article also argues that, despite a myriad of challenges, public history pushes the methodological boundary of urban preservation in China.